Attachment and emotion regulation in middle childhood: changes in affect and vagal tone during a social stress task. Issue 3 (4th May 2017) - Movahed Abtahi, Mahsa; Kerns, Kathryn A.
ABSTRACT: In middle childhood, more securely attached children show better emotion regulation when assessed as general tendencies (e.g. coping style), but studies looking at emotion in response to specific stressors have revealed mixed results. This study examined how attachment security, avoidance, and ambivalence – assessed with a story stem task (99 children, 9–11 years old) – relate to dynamic indices of affective and autonomic responses (baseline, reactivity, recovery). Reports of positive and negative affect, and high-frequency heart rate variability (HF-HRV), were assessed during a social stressor task. Securely attached children did not show reactivity effects, although they did show greater recovery of positive affect after the task ended. Avoidant children showed both less reactivity and recovery of negative affect, suggesting a dampened emotional response. Ambivalent children showed more reactivity and more recovery of negative affect. Autonomic response changes were only evident for ambivalent children, who showed less suppression of HF-HRV variability under stress.